PVDF for metal / metal ion batteries

By using a combination of fluoropolymers, the problem that electrodes and separators are difficult to ensure adhesion and flexibility in flexible batteries is solved, and the high adhesion and flexibility properties of the electrochemical device are achieved.

CN119752074APending Publication Date: 2025-04-04SOLVAY SPECIALTY POLYMERS ITALY SPA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411941242.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-10-20
Filing Date
2017-10-18
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, it is difficult to ensure good adhesion and flexibility of the electrodes simultaneously when manufacturing electrodes and separators. Especially in flexible batteries, electrochemical device components need to be able to withstand bending while maintaining excellent adhesion.

Method used

Electrodes and separators are prepared by using a combination of at least two fluoropolymers with different characteristics. Specifically, the composition (C) comprises a semi-crystalline fluoropolymer (F1) and a different fluoropolymer (F2) to improve the flexibility and adhesion of the electrode and the separator.

Benefits of technology

It realizes improved flexibility of electrodes and separators while maintaining excellent adhesion. It is suitable for applications such as flexible batteries and improves the overall performance of electrochemical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005212611490000031
    Figure BDA0005212611490000031
  • Figure BDA0005212611490000061
    Figure BDA0005212611490000061
  • Figure BDA0005212611490000062
    Figure BDA0005212611490000062
Patent Text Reader

Abstract

The present invention relates to vinylidene fluoride copolymers and fluoromonomer compositions comprising repeating units derived from hydrophilic (meth) acrylic monomers, and to their use in the manufacture of battery components, such as membrane separators and electrode binders, to said battery components and to electrochemical devices comprising said components.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with application date of October 18, 2017, application number 201780064939.6, and invention name “PVDF for Metal / Metal Ion Batteries”.

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims priority from European application number 16194835.1 filed on October 20, 2016, the entire contents of which are incorporated by reference into the present application for all purposes. Technical Field

[0004] The present invention relates to vinylidene fluoride copolymers and fluoromonomer compositions comprising repeating units derived from hydrophilic (meth)acrylic acid monomers, and to their use in the manufacture of battery components such as membrane separators and electrode adhesives, to the battery components and to electrochemical devices comprising the components. Background Art

[0005] Fluoropolymers are known in the art to be suitable as binders for making electrodes for use in electrochemical devices such as secondary batteries and as separator coatings for making composite separators.

[0006] Generally, the technology used to manufacture the positive or negative electrode and also for coating the separator involves the use of an organic solvent for dissolving the fluoropolymer.

[0007] In the case of electrode fabrication, the role of the organic solvent is typically to dissolve the fluoropolymer so as to bind the particles of electroactive material to each other and to the metal current collector when the organic solvent evaporates.

[0008] The fluoropolymer binder should suitably bind the electroactive material particles to each other and to the metal current collector so that the particles can chemically withstand large volume expansion and contraction during charge and discharge cycles.

[0009] In making the membrane, the precursor solution is typically formulated as an ink or paste comprising the solid particulate material dispersed in a solution of a fluoropolymer binder in a suitable solvent.

[0010] The ink solution thus obtained is usually arranged on the surface of a non-coated inert support, and the solvent is then removed from the solution layer to deposit a membrane layer, which adheres to the inert support. A solvent system is typically used to disperse the polymer binder, which solvent system generally includes N-methylpyrrolidone (NMP), or a mixture of N-methylpyrrolidone and a diluting solvent such as acetone, propyl acetate, methyl ethyl ketone and ethyl acetate.

[0011] PVDF is the most widely used fluoropolymer in electrode binders. For example, US2002 / 0197536 (SAMSUNG SDI CO.LTD.) 26.12.2002 discloses a polymer electrolyte for use in lithium batteries, which comprises a copolymer of vinylidene fluoride-hexafluoropropylene or a copolymer further comprising repeating units of at least one compound selected from the group consisting of acrylic acid and monoalkyl maleate.

[0012] Requirements to ensure good performance of the electrode are good adhesion of the electrode towards the current collector and good flexibility of the resulting electrode.

[0013] Similarly, a membrane with good adhesion of the coating to the inert support and good flexibility ensures good performance.

[0014] This is of particular importance in applications such as flexible batteries, where electrochemical device components must be able to withstand bending while maintaining excellent adhesion to ensure battery cell operation.

[0015] In order to obtain good quality electrodes deposited on current collectors, low viscosity electrode slurries are desirable. This makes the manufacturing process easier. Summary of the invention

[0016] It has now surprisingly been found that electrodes and separators having the desired properties described above are suitably provided by using a combination of at least two fluoropolymers having two different characteristics.

[0017] In a first embodiment, the present invention relates to a composition (C) comprising:

[0018] at least one semicrystalline fluoropolymer [polymer (F1)] comprising recurring units derived from vinylidene fluoride (VDF) in an amount of at least 50% by mole relative to the total moles of the recurring units of polymer (F1) and recurring units derived from at least one hydrophilic (meth)acrylic monomer (MA) of formula (I) in an amount of at least 0.1% by mole, preferably at least 0.3% by mole, even more preferably at least 0.5% by mole, and not more than 5% by mole relative to the total moles of the recurring units of polymer (F1):

[0019]

[0020] in:

[0021] - R1, R2 and R3, which are the same or different from each other, are independently selected from hydrogen atoms and C1-C3 hydrocarbon groups, and

[0022] -R OH is a hydrogen atom or a C1-C5 hydrocarbon moiety containing at least one hydroxyl group,

[0023] said polymer (F1) having an intrinsic viscosity, measured in dimethylformamide at 25°C, higher than 1.4 dl / g, preferably higher than 2 dl / g, even more preferably higher than 2.5 dl / g and lower than 5 dl / g; and

[0024] at least one fluoropolymer different from (F1) [polymer (F2)] comprising recurring units derived from vinylidene fluoride (VDF) in an amount of at least 50% by mole relative to the total moles of the recurring units of polymer (F2) and recurring units derived from at least one fluorinated monomer (FM) different from vinylidene fluoride in an amount of at least 2.5% by mole, preferably at least 4.0% by mole, even more preferably at least 6% by mole relative to the total moles of the recurring units of polymer (F2),

[0025] wherein polymer (F1) forms at least 10% by weight relative to the total weight of the composition (C) and polymer (F2) forms at most 90% by weight relative to the total weight of the composition (C).

[0026] In another aspect, the present invention provides a process for preparing composition (C) as described in detail above.

[0027] In another aspect, the present invention provides a method for preparing an electrode, the method comprising the steps of:

[0028] i. Providing a metal substrate having two surfaces;

[0029] ii. providing a composition (C) mixed with a liquid medium (L1) comprising a non-aqueous solvent, the composition comprising at least one polymer (F1) and at least one polymer (F2);

[0030] iii. forming an electrode slurry mixture, the mixture comprising:

[0031] - the liquid composition of step ii), and

[0032] - at least one electroactive compound;

[0033] iv. coating at least one surface of the metal substrate of step (i) with the electrode slurry mixture of step iii.;

[0034] v. Drying the coated metal substrate obtained in step iv.

[0035] In yet another aspect, the present invention provides a method for making a composite separator notably suitable for use in an electrochemical device, the method comprising the steps of:

[0036] I. providing a porous substrate having at least one surface;

[0037] II. Providing a composition (C) as defined above;

[0038] III. applying the composition (C) to at least one surface of the porous substrate to provide a coating composition layer; and

[0039] IV. Drying the coating composition layer obtained in step III. at a temperature of at least 60°C.

[0040] The present invention further provides electrodes and separators for electrochemical devices comprising the composition (C) as defined above, and electrochemical devices comprising the same. DETAILED DESCRIPTION

[0041] The applicant has surprisingly found that electrochemical device components prepared by using composition (C) as detailed above have improved flexibility while maintaining excellent adhesion to metal current collectors and separators.

[0042] Furthermore, the electrode slurry mixture comprising the composition of the present invention is characterized by a lower viscosity compared to slurries prepared by using a composition comprising exclusively a semicrystalline fluoropolymer, which makes coating of the current collector easier.

[0043] Unless otherwise indicated, in the context of the present invention, the amount of a component in a composition is expressed as the ratio between the weight of the component and the total weight of the composition multiplied by 100 (also: "wt %").

[0044] As used herein, the term "semi-crystalline" means a fluoropolymer having at least one crystalline melting point on DSC analysis in addition to the glass transition temperature, Tg. For the purposes of the present invention, a semi-crystalline fluoropolymer is herein intended to mean a fluoropolymer having a heat of fusion of from 10 J / g to 90 J / g, preferably from 30 J / g to 80 J / g, more preferably from 35 J / g to 75 J / g, as measured according to ASTM D3418-08.

[0045] As used herein, the terms "adheres" and "adhesion" mean that two layers are permanently attached to each other via their contacting surfaces, such as classified as 5B to 3B in a cross-cut test according to ASTM D3359 Test Method B.

[0046] As used herein, the term "electrode" refers to a layer comprising a binder, typically formed of a polymer material, and an electroactive compound.

[0047] For the purposes of the present invention, the term "electroactive compound" is intended to mean a compound capable of incorporating or inserting into its structure and substantially releasing alkali or alkaline earth metal ions therefrom during the charge and discharge phases of an electrochemical device. The electroactive compound is preferably capable of incorporating or inserting and releasing lithium ions.

[0048] The term "membrane" is intended herein to mean a porous polymer material that electrically and physically separates electrodes of opposite polarity in an electrochemical device and is permeable to ions flowing therebetween.

[0049] The term "electrochemical device" is intended herein to mean an electrochemical cell comprising a positive electrode, a negative electrode and a liquid electrolyte, wherein a single-layer or multi-layer separator is adhered to at least one surface of one of the electrodes.

[0050] Non-limiting examples of suitable electrochemical devices include notably secondary batteries, especially alkali metal or alkaline earth metal secondary batteries, such as lithium ion batteries, and capacitors, especially lithium ion based capacitors and electric double layer capacitors ("supercapacitors").

[0051] For the purposes of the present invention, "secondary battery" is intended to mean a rechargeable battery. Non-limiting examples of secondary batteries include, notably, alkali metal or alkaline earth metal secondary batteries.

[0052] The term "repeating unit derived from vinylidene fluoride (also generally denoted as vinylidene fluoride, 1,1-difluoroethylene, VDF)" is intended to mean a repeating unit having formula (I):

[0053] CF2=CH 2。

[0054] The hydrophilic (meth)acrylic monomer (MA) preferably conforms to the following formula (II):

[0055]

[0056] Wherein R1, R2 and R3, which are the same or different from each other, are each independently a hydrogen atom or a C1-C3 hydrocarbon group. Non-limiting examples of hydrophilic (meth) acrylic monomers (MA) notably include:

[0057] -Acrylic acid (AA)

[0058] - (meth)acrylic acid,

[0059] - Hydroxyethyl (meth)acrylate (HEA) having the formula:

[0060]

[0061] - 2-Hydroxypropyl acrylate (HPA) having the formula:

[0062]

[0063] -Hydroxyethylhexyl (meth)acrylate,

[0064] and mixtures thereof.

[0065] Still more preferably, the hydrophilic (meth)acrylic monomer (MA) is acrylic acid (AA).

[0066] The term "fluorinated monomer (FM)" is intended herein to mean an ethylenically unsaturated monomer comprising at least one fluorine atom.

[0067] In the remainder of the text, the expressions "fluorinated monomer" are to be understood for the purposes of the present invention both in the plural and in the singular, ie they denote both one or more than one fluorinated monomer as defined above.

[0068] If the fluorinated monomer (FM) comprises at least one hydrogen atom, it is designated as hydrogen-containing fluorinated monomer.

[0069] If the fluorinated monomer (FM) contains no hydrogen atoms, it is designated as a per(halo)fluorinated monomer.

[0070] The fluorinated monomer (FM) may further comprise one or more other halogen atoms (Cl, Br, I).

[0071] Non-limiting examples of suitable fluorinated monomers (FM) include notably the following:

[0072] - C2-C8 perfluoroolefins, such as tetrafluoroethylene and hexafluoropropylene (HFP);

[0073] - C2-C8 hydrogenated fluoroolefins, such as vinyl fluoride, 1,2-difluoroethylene and trifluoroethylene;

[0074] - having the formula CH2=CH-R f0 Perfluoroalkylethylene, where R f0 is a C1-C6 perfluoroalkyl group;

[0075] - chloro- and / or bromo- and / or iodo-C2-C6-fluoroolefins, such as chlorotrifluoroethylene;

[0076] -Has the formula CF2=CFOR f1 (per)fluoroalkyl vinyl ether, wherein Rf1 is C1-C6 fluoro- or perfluoroalkyl, such as CF3, C2F5, C3F7;

[0077] -CF2=CFOX0 (per)fluoro-oxyalkyl vinyl ether, wherein X0 is C1-C 12 Alkyl, C1-C 12 Oxyalkyl or C1-C 12 (Per)fluorooxyalkyl, such as perfluoro-2-propoxy-propyl;

[0078] -Has the formula CF2=CFOCF2OR f2 (per)fluoroalkyl vinyl ether, wherein R f2 is a C1-C6 fluoro- or perfluoroalkyl group, such as CF3, C2F5, C3F7, or a C1-C6 (per)fluorooxyalkyl group having one or more ether groups, such as -C2F5-O-CF3;

[0079] - a functional (per)fluoro-oxyalkyl vinyl ether of the formula CF2=CFOY0, wherein Y0 is C1-C 12 Alkyl or (per) fluoroalkyl, C1-C 12 Oxyalkyl or C1-C 12 (per)fluorooxyalkyl, and Y0 comprises a carboxylic acid or sulfonic acid group (in the form of its acid, acid halide or salt);

[0080] - fluorodioxole, preferably perfluorodioxole.

[0081] The fluorinated monomer (FM) is preferably hexafluoropropylene (HFP).

[0082] The inventors have found that the best results are obtained when the polymer (F1) is a linear semi-crystalline copolymer.

[0083] The term "linear" is intended to mean a copolymer consisting of an essentially linear sequence of repeating units from (VDF) monomers and (MA) monomers; polymer (F1 ) can thus be distinguished from graft and / or comb polymers.

[0084] The determination of the molar percentage of recurring units derived from at least one functional hydrogenated monomer in the polymer (F1) can be carried out by any suitable method. Mention may notably be made of the acid-base titration method or the NMR method.

[0085] The polymer (F1) more preferably comprises repeating units derived from:

[0086] at least 50% by mole, preferably at least 75% by mole, more preferably at least 85% by mole of vinylidene fluoride (VDF),

[0087] - from 0.1 to 5% by mole, preferably from 0.3 to 1.5% by mole, more preferably from 0.5 to 1% by mole of at least one hydrophilic (meth)acrylic monomer (MA).

[0088] The polymer (F1) is typically obtainable by emulsion polymerization or suspension polymerization of at least one vinylidene fluoride monomer and at least one hydrophilic (meth)acrylic monomer.

[0089] The polymer (F2) is typically obtainable by emulsion polymerization or suspension polymerization of at least one vinylidene fluoride monomer and at least one fluorinated monomer (FM).

[0090] In case polymer (F2) contains recurring units derived from at least one hydrophilic (meth)acrylic monomer (MA), said recurring units (MA) are preferably contained in an amount of at least 0.05% by mole, more preferably at least 0.1% by mole, even more preferably at least 0.2% by mole and at most 10% by mole, more preferably at most 7.5% by mole, even more preferably at most 3% by mole, relative to the total moles of recurring units of polymer (F2).

[0091] The inventors have found that a substantially random distribution of monomer (MA) on the polyvinylidene fluoride backbone of polymer (F1) advantageously maximizes the effect of the monomer (MA) on both the adhesive and / or hydrophilic behavior of the resulting copolymer, even at low levels of monomer (MA) in the composition, without compromising other outstanding properties of vinylidene fluoride polymers, such as thermal stability and mechanical properties.

[0092] At least another fluorinated monomer (FM2) different from (FM) and VDF may be included in polymers (F1) and (F2).

[0093] Such monomer (FM2) may include at least one conventionally used monomer copolymerizable with vinylidene fluoride, such as, but not limited to, vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene (CTFE), tetrafluoroethylene (TFE), hexafluoropropylene (HFP) and fluoroalkyl vinyl ethers and mixtures thereof.

[0094] The amount of monomer (FM2) in polymer (F1) and in polymer (F2) is preferably less than 10 mol%, more preferably less than 5 mol% or less than 2 mol% relative to the total molar number of repeating units in polymer (F1) or polymer (F2), respectively.

[0095] In a preferred embodiment of the present invention, )F1) is a copolymer of VDF-MA, wherein the content of the hydrophilic (meth)acrylic monomer having formula (I) is contained in an amount between 0.3 mol % and 1.5 mol % relative to the total moles of the repeating units of polymer (F1).

[0096] More preferably, the hydrophilic (meth)acrylic monomer (MA) is a hydrophilic (meth)acrylic monomer having formula (II), still more preferably, it is acrylic acid (AA) and (F1) is a VDF-AA copolymer.

[0097] In a preferred embodiment of the present invention, )F2) is a copolymer of VDF and a fluorinated monomer, wherein the fluorinated monomer is contained in an amount between 2.5% by mole and 10% by mole relative to the total moles of the repeating units of polymer (F2).

[0098] More preferably, the fluorinated monomer (FM) is hexafluoropropylene (HFP) and (F2) is a VDF-HFP copolymer.

[0099] In composition (C), polymer (F1) preferably forms at least 25% by weight and polymer (F2) forms at most 75% by weight relative to the total weight of composition (C).

[0100] Composition (C) is typically provided in the form of a powder.

[0101] In another aspect, the present invention provides a process for preparing a composition (C) as above detailed, said process comprising the step of mixing the at least one polymer (F1) with the at least one polymer (F2).

[0102] In a preferred embodiment of the present invention, polymer (F2) has an intrinsic viscosity measured in dimethylformamide at 25°C lower than that of polymer (F1 ), preferably lower than 2 dl / g, more preferably lower than 1.7 dl / g.

[0103] In another aspect, the present invention provides a method for preparing an electrode, the method comprising the steps of:

[0104] i. Providing a metal substrate having two surfaces;

[0105] ii. providing a composition (C) mixed with a liquid medium (L1) comprising a non-aqueous solvent, the composition comprising at least one polymer (F1) and at least one polymer (F2);

[0106] iii. forming an electrode slurry mixture, the mixture comprising:

[0107] - the liquid composition of step ii), and

[0108] - at least one electroactive compound;

[0109] iv. coating at least one surface of the metal substrate of step (ii) with the electrode slurry mixture of step iii.;

[0110] v. Drying the coated metal substrate obtained in step iv.

[0111] The metal substrate is typically a foil, screen or mesh made of a metal such as copper, aluminum, iron, stainless steel, nickel, titanium or silver.

[0112] In general, the technology for making electrodes includes using a solvent such as an organic solvent (such as N-methyl-2-pyrrolidone (NMP)) to dissolve the VDF polymer binder and homogenize them with powdered electrode materials and all other suitable components to produce a paste applied to a metal collector (such as an aluminum collector). Non-limiting examples of electrodes and methods for their manufacture are described in WO 2013 / 010936A (SOLVAY SPECIALTY POLYMERS ITALY) 1 / 24 / 2013 and in references cited herein.

[0113] In step ii. of the process of the invention, suitable non-aqueous solvents include notably the following: N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, hexamethylphosphoramide, dioxane, tetrahydrofuran, tetramethylurea, triethyl phosphate, trimethyl phosphate and mixtures thereof.

[0114] In step iii. of the method of the present invention, the electrode slurry mixture may further comprise:

[0115] - at least one conductive agent,

[0116] - at least one additive, and

[0117] - At least one viscosity-modifying agent.

[0118] Non-limiting examples of suitable additives include notably additives that impart electrical conductivity and / or thickeners.

[0119] In step iv. of the method of the present invention, the electrode slurry mixture provided by step iii. is applied to at least one surface of the metal substrate by techniques generally known in the art (such as by casting, brushing, roller coating, inkjet coating, squeegee, foam coater, curtain coating, vacuum coating, spraying).

[0120] In yet another aspect, the present invention provides a method for making a composite separator notably suitable for use in an electrochemical device, the method comprising the steps of:

[0121] I. providing a porous substrate having at least one surface;

[0122] II. Providing a composition (C) as defined above;

[0123] III. applying the composition (C) to at least one surface of the porous substrate to provide a coating composition layer; and

[0124] IV. Drying the coating composition layer at a temperature of at least 60° C. to provide the composite separator.

[0125] In step III. of the process of the present invention, the composition (C) is typically applied to at least one surface of the porous substrate by a technique selected from the group consisting of casting, spraying, roller coating, doctor blade coating, slot coating, gravure coating, inkjet printing, spin coating and screen printing, brush coating, roller brush, foam coater, curtain coating, vacuum coating.

[0126] Non-limiting examples of suitable porous substrates include, notably, porous membranes made of inorganic, organic and naturally occurring materials, and in particular made of nonwoven fibers (cotton, polyamide, polyester, glass), made of polymers (polyethylene, polypropylene, poly(tetrafluoroethylene), poly(vinyl chloride)), and made of certain fibrous naturally occurring substances (e.g., asbestos).

[0127] Favorable results have been obtained when the porous support is a polyolefin porous support, such as a polyethylene or polypropylene porous support.

[0128] In step V. of the process according to the invention, the layer of coating composition is dried.

[0129] The drying temperature is typically comprised between 60 and 200°C, preferably between 70 and 180°C.

[0130] Should the disclosure of any patents, patent applications, and publications incorporated by reference into this application conflict with the description of this application to the extent that it renders a term unclear, this description shall take precedence.

[0131] 1. A composition (C), comprising:

[0132] at least one semicrystalline fluoropolymer, polymer (F1), comprising recurring units derived from vinylidene fluoride (VDF) in an amount of at least 50% by mole relative to the total moles of the recurring units of polymer (F1) and recurring units derived from at least one functional hydrogenated monomer comprising at least one hydrophilic (meth)acrylic monomer (MA) of formula (I) in an amount of at least 0.1% by mole, preferably at least 0.3% by mole, even more preferably at least 0.5% by mole, and not more than 5% by mole relative to the total moles of the recurring units of polymer (F1):

[0133]

[0134] in:

[0135] - R1, R2 and R3, which are the same or different from each other, are independently selected from hydrogen atoms and C1-C3 hydrocarbon groups, and

[0136] -R OH is a hydrogen atom or a C1-C5 hydrocarbon moiety containing at least one hydroxyl group,

[0137] said polymer (F1) having an intrinsic viscosity, measured in dimethylformamide at 25°C, higher than 1.4 dl / g, preferably higher than 2 dl / g, even more preferably higher than 2.5 dl / g and lower than 5 dl / g; and

[0138] at least one fluoropolymer different from (F1), polymer (F2), comprising recurring units derived from vinylidene fluoride (VDF) in an amount of at least 50% by mole relative to the total moles of the recurring units of polymer (F2) and recurring units derived from at least one fluorinated monomer (FM) different from vinylidene fluoride in an amount of at least 2.5% by mole, preferably at least 4.0% by mole, even more preferably at least 6% by mole relative to the total moles of the recurring units of polymer (F2),

[0139] wherein polymer (F1) forms at least 10% by weight relative to the total weight of the composition (C) and polymer (F2) forms at most 90% by weight relative to the total weight of the composition (C).

[0140] 2. The composition (C) according to embodiment 1, wherein the at least one hydrophilic (meth)acrylic monomer (MA) conforms to the following formula (II):

[0141]

[0142] 3. The composition (C) according to embodiment 2, wherein the at least one hydrophilic (meth)acrylic monomer (MA) having formula (II) is selected from the group consisting of acrylic acid, (meth)acrylic acid, hydroxyethyl (meth)acrylate, 2-hydroxypropyl acrylate, hydroxyethylhexyl (meth)acrylate and mixtures thereof.

[0143] 4. The composition (C) according to any one of the preceding embodiments, wherein polymer (F1) comprises repeating units derived from:

[0144] at least 50% by mole, preferably at least 75% by mole, more preferably at least 85% by mole of vinylidene fluoride (VDF),

[0145] - from 0.1 to 5% by mole, preferably from 0.3 to 1.5% by mole, more preferably from 0.5 to 1% by mole of at least one hydrophilic (meth)acrylic monomer (MA).

[0146] 5. The composition (C) according to any one of the preceding embodiments, wherein the fluorinated monomer (FM) is selected from the group consisting of:

[0147] - C2-C8 perfluoroolefins, such as tetrafluoroethylene and hexafluoropropylene (HFP);

[0148] - C2-C8 hydrogenated fluoroolefins, such as vinyl fluoride, 1,2-difluoroethylene and trifluoroethylene;

[0149] - having the formula CH2=CH-R f0 Perfluoroalkylethylene, where R f0 is a C1-C6 perfluoroalkyl group;

[0150] - chloro- and / or bromo- and / or iodo-C2-C6-fluoroolefins, such as chlorotrifluoroethylene;

[0151] -Has the formula CF2=CFOR f1 (per)fluoroalkyl vinyl ether, wherein R f1 is C1-C6 fluoro- or perfluoroalkyl, such as CF3, C2F5, C3F7;

[0152] -CF2=CFOX0 (per)fluoro-oxyalkyl vinyl ether, wherein X0 is C1-C 12 Alkyl, C1-C 12 Oxyalkyl or C1-C 12 (Per)fluorooxyalkyl, such as perfluoro-2-propoxy-propyl;

[0153] -Has the formula CF2=CFOCF2OR f2(per)fluoroalkyl vinyl ether, wherein R f2 is a C1-C6 fluoro- or perfluoroalkyl group, such as CF3, C2F5, C3F7, or a C1-C6 (per)fluorooxyalkyl group having one or more ether groups, such as -C2F5-O-CF3;

[0154] - a functional (per)fluoro-oxyalkyl vinyl ether of the formula CF2=CFOY0, wherein Y0 is C1-C 12 Alkyl or (per) fluoroalkyl, C1-C 12 Oxyalkyl or C1-C 12 (per)fluorooxyalkyl, and Y0 comprises a carboxylic acid or sulfonic acid group (in the form of its acid, acid halide or salt);

[0155] - fluorodioxole, preferably perfluorodioxole.

[0156] 6. Composition (C) according to any one of the preceding embodiments, wherein the fluorinated monomer (FM) is hexafluoropropylene (HFP).

[0157] 7. Composition (C) according to any of the preceding embodiments, wherein polymer (F1) forms at least 25% by weight relative to the total weight of the composition (C) and polymer (F2) forms at most 75% by weight relative to the total weight of the composition (C).

[0158] 8. Composition (C) according to any of the preceding embodiments, wherein polymer (F2) has an intrinsic viscosity measured in dimethylformamide at 25°C lower than that of polymer (F1), preferably lower than 2 dl / g, more preferably lower than 1.7 dl / g.

[0159] 9. A method for preparing an electrode, the method comprising the following steps:

[0160] i. Providing a metal substrate having two surfaces;

[0161] ii. providing a composition (C) according to embodiments 1 to 8 mixed with a liquid medium (L1) comprising a non-aqueous solvent;

[0162] iii. forming an electrode slurry mixture, the mixture comprising:

[0163] - the liquid composition of step ii), and

[0164] - at least one electroactive compound;

[0165] iv. coating at least one surface of the metal substrate of step i. with the electrode slurry mixture of step iii.;

[0166] v. Drying the coated metal substrate obtained in step iv.

[0167] 10. A method for preparing a composite membrane, the method comprising the following steps:

[0168] I. providing a porous substrate having at least one surface;

[0169] II. Providing a composition (C) according to embodiments 1 to 8;

[0170] III. applying the composition (C) to at least one surface of the porous substrate to provide a coating composition layer; and

[0171] IV. Drying the coating composition layer obtained in step III. at a temperature of at least 60°C.

[0172] 11. An electrode comprising the composition (C) according to any one of embodiments 1 to 8.

[0173] 12. A composite membrane comprising the composition (C) according to any one of embodiments 1 to 8.

[0174] 13. An electrochemical device comprising the electrode according to embodiment 11.

[0175] 14. An electrochemical device comprising the composite separator according to embodiment 12.

[0176] The present invention will now be described with reference to the following examples, which are intended to be illustrative only and are not intended to limit the scope of the present invention.

[0177] Experimental Section

[0178] raw materials

[0179] Polymer (F1): VDF-AA (0.9% by mole) polymer having an intrinsic viscosity of 3.0 dl / g in DMF at 25°C (hereinafter Polymer (F1)-A).

[0180] Polymer (F1): VDF-AA (0.6% by mole) polymer having an intrinsic viscosity of 3.8 dl / g in DMF at 25°C (hereinafter Polymer (F1)-B).

[0181] Polymer (F2): VDF-HFP (7% by mole) polymer having an intrinsic viscosity of 1.4 dl / g in DMF at 25°C.

[0182] Determination of the intrinsic viscosity of polymers (in DMF at 25°C)

[0183] The intrinsic viscosity is determined on the basis of the falling time at 25° C. of a solution at a concentration of about 0.2 g / dl obtained by dissolving the polymer (F1) or the polymer (F2) in dimethylformamide in an Ubbelhode viscometer using the following equation:

[0184]

[0185] Where c is the polymer concentration in g / dl;

[0186] ηr is the relative viscosity, i.e., the ratio between the falling time of the sample solution and the falling time of the solvent;

[0187] ηsp is the specific viscosity, i.e. ηr-1;

[0188] Γ is the experimental factor, which corresponds to 3.

[0189] Example 1: Preparation of a composition (C) according to the invention

[0190] Four compositions comprising different amounts of polymer (F1)-A or polymer (F1)-B and polymer (F2) were prepared in a Henschel mixer (model FML 40) with command MINICON S210 at 1500 rpm for 5 min.

[0191] These powders were loaded at room temperature.

[0192] Composition (a) comprises 55% by weight of polymer (F1)-A and 45% by weight of polymer (F2), relative to the total weight of the composition.

[0193] Composition (b) comprises 70% by weight of polymer (F1)-A and 30% by weight of polymer (F2), relative to the total weight of the composition.

[0194] Composition (c) comprises 85% by weight of polymer (F1)-A and 15% by weight of polymer (F2), relative to the total weight of the composition.

[0195] Composition (d) comprises 30% by weight of polymer (F1)-B and 70% by weight of polymer (F2), relative to the total weight of the composition.

[0196] Preparation of electrode slurry mixture

[0197] The electrode slurry mixture was prepared by dissolving 1 g of the powder of the composition (a), composition (b), composition (c), and composition (d) of polymer (F1)-A, polymer (F1)-B, and polymer (F2) in 25 g of NMP at room temperature under stirring to obtain a clear solution. Under gentle stirring, 1 g of carbon black (C-NERGY Super C65 from Imerys) and 18 g of LiCoO2 (C-NERGY Super C65 from Umicore) were mixed using a Dispermat mixing device. LCO D10) was added and the slurries were mixed thoroughly to ensure good homogeneity.

[0198] The percentage of solids in the electrode slurries is 40% by weight, the composition (C) accounts for 5% by weight of the total solid components, carbon black is 5% by weight and LiCoO2 is 90% by weight.

[0199] Slurry viscosity

[0200] The slurry viscosity was measured using a rotational rheometer model from Anton Paar QC measurement. Measurements were performed at 25°C. The reported -1 The viscosity value at the shear rate.

[0201] Preparation of electrodes

[0202] The cathode was prepared by casting the previously prepared slurry on Al metal foil. The coating was finally dried in a vacuum oven at 130°C for sufficient time to ensure solvent removal. The coating thickness was set to obtain a final electrode thickness of approximately 65 μm.

[0203] Adhesion measurement on electrodes

[0204] The adhesion of the electrode mixture coating on the metal foil was evaluated by performing a peel test following standard ASTM D903.

[0205] Flexible methods and measurements

[0206] Electrode flexibility was evaluated by the mandrel bend test method derived from ASTM D 3111-99. Test strips of the properly sized and conditioned electrode were bent 180° several times on a 2-mm diameter mandrel (rod) until cracks became apparent in the electrode. The higher the number of bends, the higher the electrode flexibility.

[0207] Table 1

[0208]

[0209] These results show that the compositions according to the invention (compositions (a) to (d)) have good values ​​of adhesion to the electrode, comparable to the values ​​of adhesion of polymer (F1) alone.

[0210] Furthermore, the composition of the present invention imparts high flexibility to an electrode prepared by coating the metal foil with the composition.

Claims

1. A composition (C), comprising: at least one semicrystalline fluoropolymer, polymer (F1), comprising recurring units derived from vinylidene fluoride (VDF) in an amount of at least 50% by mole relative to the total moles of the recurring units of polymer (F1) and recurring units derived from at least one functional hydrogenated monomer comprising at least one hydrophilic (meth)acrylic monomer (MA) of formula (I) in an amount of at least 0.1% by mole, preferably at least 0.3% by mole, even more preferably at least 0.5% by mole, and not more than 5% by mole relative to the total moles of the recurring units of polymer (F1): in: - R1, R2 and R3, which are the same or different from each other, are independently selected from hydrogen atoms and C1-C3 hydrocarbon groups, and -R OH is a hydrogen atom or a C1-C5 hydrocarbon moiety containing at least one hydroxyl group, said polymer (F1) having an intrinsic viscosity, measured in dimethylformamide at 25°C, higher than 1.4 dl / g, preferably higher than 2 dl / g, even more preferably higher than 2.5 dl / g and lower than 5 dl / g; and at least one fluoropolymer different from (F1), polymer (F2), comprising recurring units derived from vinylidene fluoride (VDF) in an amount of at least 50% by mole relative to the total moles of the recurring units of polymer (F2) and recurring units derived from at least one fluorinated monomer (FM) different from vinylidene fluoride in an amount of at least 2.5% by mole, preferably at least 4.0% by mole, even more preferably at least 6% by mole relative to the total moles of the recurring units of polymer (F2), wherein polymer (F1) forms at least 10% by weight relative to the total weight of the composition (C) and polymer (F2) forms at most 90% by weight relative to the total weight of the composition (C).

2. The composition (C) according to claim 1, wherein the at least one hydrophilic (meth)acrylic monomer (MA) conforms to the following formula (II):

3. The composition (C) according to claim 2, wherein the at least one hydrophilic (meth) acrylic monomer (MA) having formula (II) is selected from the group consisting of: Acrylic acid, (meth)acrylic acid, hydroxyethyl (meth)acrylate, 2-hydroxypropyl acrylate, hydroxyethylhexyl (meth)acrylate, and mixtures thereof.

4. Composition (C) according to any one of the preceding claims, wherein polymer (F1) comprises repeating units derived from: at least 50% by mole, preferably at least 75% by mole, more preferably at least 85% by mole of vinylidene fluoride (VDF), - from 0.1 to 5% by mole, preferably from 0.3 to 1.5% by mole, more preferably from 0.5 to 1% by mole of at least one hydrophilic (meth)acrylic monomer (MA).

5. Composition (C) according to any one of the preceding claims, wherein the fluorinated monomer (FM) is selected from the group consisting of: - C2-C8 perfluoroolefins, such as tetrafluoroethylene and hexafluoropropylene (HFP); - C2-C8 hydrogenated fluoroolefins, such as vinyl fluoride, 1,2-difluoroethylene and trifluoroethylene; - having the formula CH2=CH-R f0 Perfluoroalkylethylene, where R f0 is a C1-C6 perfluoroalkyl group; - chloro- and / or bromo- and / or iodo-C2-C6-fluoroolefins, such as chlorotrifluoroethylene; -Has the formula CF2=CFOR f1 (per)fluoroalkyl vinyl ether, wherein R f1 is C1-C6 fluoro- or perfluoroalkyl, such as CF3, C2F5, C3F7; -CF2=CFOX0 (per)fluoro-oxyalkyl vinyl ether, wherein X0 is C1-C 12 Alkyl, C1-C 12 Oxyalkyl or C1-C 12 (Per)fluorooxyalkyl, such as perfluoro-2-propoxy-propyl; -Has the formula CF2=CFOCF2OR f2 (per)fluoroalkyl vinyl ether, wherein R f2 is a C1-C6 fluoro- or perfluoroalkyl group, such as CF3, C2F5, C3F7, or a C1-C6 (per)fluorooxyalkyl group having one or more ether groups, such as -C2F5-O-CF3; - a functional (per)fluoro-oxyalkyl vinyl ether of the formula CF2=CFOY0, wherein Y0 is C1-C 12 Alkyl or (per) fluoroalkyl, C1-C 12 Oxyalkyl or C1-C 12 (per)fluorooxyalkyl, and Y0 comprises a carboxylic acid or sulfonic acid group (in the form of its acid, acid halide or salt); - fluorodioxole, preferably perfluorodioxole.

6. Composition (C) according to any one of the preceding claims, wherein the fluorinated monomer (FM) is hexafluoropropylene (HFP).

7. Composition (C) according to any of the preceding claims, wherein polymer (F1) forms at least 25% by weight relative to the total weight of composition (C) and polymer (F2) forms at most 75% by weight relative to the total weight of the composition (C).

8. Composition (C) according to any of the preceding claims, wherein polymer (F2) has an intrinsic viscosity measured in dimethylformamide at 25°C lower than that of polymer (F1 ), preferably lower than 2 dl / g, more preferably lower than 1.7 dl / g.

9. A method for preparing an electrode, the method comprising the following steps: i. Providing a metal substrate having two surfaces; ii. providing a composition (C) according to claims 1 to 8 mixed with a liquid medium (L1) comprising a non-aqueous solvent; iii. forming an electrode slurry mixture, the mixture comprising: - the liquid composition of step ii), and - at least one electroactive compound; iv. coating at least one surface of the metal substrate of step i. with the electrode slurry mixture of step iii.; v. Drying the coated metal substrate obtained in step iv.

10. A method for preparing a composite membrane, the method comprising the following steps: I. providing a porous substrate having at least one surface; II. Providing a composition (C) according to claims 1 to 8; III. applying the composition (C) to at least one surface of the porous substrate to provide a coating composition layer; and IV. Drying the coating composition layer obtained in step III. at a temperature of at least 60°C.

11. An electrode comprising the composition (C) according to any one of claims 1 to 8.

12. A composite separator comprising the composition (C) according to any one of claims 1 to 8.

13. An electrochemical device comprising the electrode according to claim 11.

14. An electrochemical device comprising the composite separator according to claim 12.

Citation Information

Patent Citations

  • Lithium polymer battery

    US20020197536A1

  • Aqueous vinylidene fluoride polymer latex

    WO2013010936A1